Guadecitabine vs treatment choice in newly diagnosed acute myeloid leukemia: a global phase 3 randomized study - Fenaux, Pierre; Gobbi, Marco; Kropf, Patricia L; Issa, Jean-Pierre J; Roboz, Gail J; Mayer, Jiri; Krauter, Jürgen; Robak, Tadeusz; Kantarjian, Hagop; Novak, Jan; Jedrzejczak, Wieslaw W; Thomas, Xavier; et al. (Blood advances, 2023)
This phase 3 study evaluated the efficacy and safety of the new hypomethylating agent guadecitabine (n = 408) vs a preselected treatment choice (TC; n = 407) of azacitidine, decitabine, or low-dose cytarabine in patients with acute myeloid leukemia unfit to receive intensive induction chemotherapy. Half of the patients (50%) had poor Eastern Cooperative Oncology Group Performance Status (2-3). The coprimary end points were complete remission (19% and 17% of patients for guadecitabine and TC, respectively [stratified P = .48]) and overall survival (median survival 7.1 and 8.5 months for guadecitabine and TC, respectively [hazard ratio, 0.97; 95% confidence interval, 0.83-1.14; stratified log-rank P = .73]). One- and 2-year survival estimates were 37% and 18% for guadecitabine and 36% and 14% for TC, respectively. A large proportion of patients (42%) received <4 cycles of treatment in both the arms. In a post hoc analysis of patients who received ≥4 treatment cycles, guadecitabine was associated with longer median survival vs TC (15.6 vs 13.0 months [hazard ratio, 0.78; 95% confidence interval, 0.64-0.96; log-rank P = .02]). There was no significant difference in the proportion of patients with grade ≥3 adverse events (AEs) between guadecitabine (92%) and TC (88%); however, grade ≥3 AEs of febrile neutropenia, neutropenia, and pneumonia were higher with guadecitabine. In conclusion, no significant difference was observed in the efficacy of guadecitabine and TC in the overall population. This trial was registered at www.clinicaltrials.gov as #NCT02348489.
Keywords: cytarabin; akutní myeloidní leukemie; Cytarabine; lidé; azacytidin; Azacitidine; Treatment Outcome; výsledek terapie; Leukemia, Myeloid, Acute; Humans